2011
DOI: 10.1007/s11665-011-9875-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Material-Model Development for Microphase-Segregated Polyurea: An Overview

Abstract: Numerous experimental investigations reported in the open literature over the past decade have clearly demonstrated that the use of polyurea external coatings and/or inner layers can substantially enhance both the blast resistance (the ability to withstand shock loading) and the ballistic performance (the ability to defeat various high-velocity projectiles such as bullets, fragments, shrapnel, etc. without penetration, excessive deflection or spalling) of buildings, vehicles, combat-helmets, etc. It is also we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 35 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…To obtain these relations, a separate set of finite element analyses was carried out in which a single-material parallelepiped shaped slug (subjected to zero lateral-strain boundary conditions) impacts (at a zero obliquity angle) a rigid wall. More details regarding this type of finite element analyses can be found in our recent work (Grujicic et al, 2010b). Slug-rigid wall collision results in:…”
Section: Brief Discussionmentioning
confidence: 99%
“…To obtain these relations, a separate set of finite element analyses was carried out in which a single-material parallelepiped shaped slug (subjected to zero lateral-strain boundary conditions) impacts (at a zero obliquity angle) a rigid wall. More details regarding this type of finite element analyses can be found in our recent work (Grujicic et al, 2010b). Slug-rigid wall collision results in:…”
Section: Brief Discussionmentioning
confidence: 99%
“…Polyurea has been reported as a good candidate for impulsive loading applications since it has been demonstrated that it is intrinsically reinforced by its morphology, consisting of a continuous rubbery soft matrix containing well dispersed nanoscaled hard domains . Recent studies proved that a polyurea coated steel plate could suffer lower deformations than an uncoated one when subjected to impulsive loading .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of these conjugated polymers to amplify their sensitivity on fluorescence responses is attributed to the efficient electronic delocalization and rapid transport of excitons along the π‐ conjugated backbone. Much research has been done on polyureas due to their outstanding thermal and mechanical properties 3–9. However, to our knowledge, fabrication of solid‐state electrofluorescent devices (EFD) using PU based materials has not been examined and reported.…”
Section: Introductionmentioning
confidence: 99%